A structure in the early Universe at z similar to 1.3 that exceeds the homogeneity scale of the R-W concordance cosmology - Clowes, R; Harris, K; Raghunathan, S; Campusano, L; Soechting, I; Graham, M (2013)
A large quasar group (LQG) of particularly large size and high membership has been identified in theDR7QSO catalogue of the Sloan Digital Sky Survey. It has characteristic size (volume1/3) ~ 500 Mpc (proper size, present epoch), longest dimension ~1240 Mpc, membership of 73 quasars and mean redshift -z = 1.27. In terms of both size and membership, it is the most extreme LQG found in the DR7QSO catalogue for the redshift range 1.0 ≤ z ≤ 1.8 of our current investigation. Its location on the sky is~8. {ring operator} 8 north (~615 Mpc projected) of the Clowes and Campusano LQG at the same redshift, -z = 1.28, which is itself one of the more extreme examples. Their boundaries approach to within ~2{ring operator} (~140 Mpc projected). This new, Huge-LQG appears to be the largest structure currently known in the early Universe. Its size suggests incompatibility with the Yadav et al. scale of homogeneity for the concordance cosmology, and thus challenges the assumption of the cosmological principle. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.